SPATIAL ANALYSIS OF HYDROMETEOROLOGICAL VULNERABILITY OF NATURAL DISASTERS IN THE BOGOR REGION - Fuad Alkaesi; Isman Kadar; Yossa Istiadi (Journal of Science Innovare, 2021)
Bogor Regency has a fairly large potential for natural disasters in the province of West Java, particularly hydrometeorological natural disasters, floods, and landslides. According to the Bogor Regency BPBD, there are 15 sub-districts with high potential for natural disasters. If we look at the level of damage, natural disasters, floods, and landslides have a very high level of loss due to the lack of information obtained by the community on the possibility of disasters occurring nearby. To avoid disaster losses, disaster risk management measures are needed. One way to manage disaster risk is to perform spatial data analysis in the form of maps of areas potentially prone to flooding and landslides based on the parameters that cause flooding and landslides. The method used in this study is Weighted Scoring and the analysis of disaster risk data is done spatially using a geographic information system (GIS) with the help of ArcGIS Software. This study aims to analyze and map the potential distribution of vulnerability to runoff and landslides in the district of Bogor. The results of the analysis are maps of areas prone to runoff and landslides in the regency of Bogor which can be used as a reference for mitigating natural disasters as well as for recommendations in regional land use planning.